Influencia de plataformas virtuales en la Economia de las PYMES en las familias del asentamiento humano Villa Primavera, Sullana-2020 - Masias Rugel, Xiomara de los Milagros (2024)
This research addresses the problem of insufficient technological infrastructure in Small and Medium Enterprises (SMEs) of the Villa Primavera Human Settlement. The main purpose of this study is to determine the impact of virtual platforms on the economy of SMEs, therefore, on the economic well-being of the families of Villa Primavera, Sullana, during the year 2020. Through a descriptive methodology and a design not cross-sectional experimental, a survey was applied as the primary instrument for data collection. The results indicate that 95% of participating companies aspire to increase their economic benefits. WhatsApp emerges as the most prevalent application among its commercial operations, as well as 86% of SMEs express the desire to expand their digital presence by developing their own website. All respondents recognize the importance of quality customer service, prioritizing efficiency in their business practices. It is concluded that virtual platforms exert a significant influence on the economy of SMEs in Villa Primavera, not only by facilitating the increase in profits through sales, but also by optimizing customer service, reducing costs in marketing and human resources, thus improving operational efficiency